2017
DOI: 10.1016/j.celrep.2017.11.096
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 Is a Critical Regulator of Breast Cancer Stem Cell Function via Histone Methylation and FOXP1 Expression

Abstract: SummaryBreast cancer progression, treatment resistance, and relapse are thought to originate from a small population of tumor cells, breast cancer stem cells (BCSCs). Identification of factors critical for BCSC function is therefore vital for the development of therapies. Here, we identify the arginine methyltransferase PRMT5 as a key in vitro and in vivo regulator of BCSC proliferation and self-renewal and establish FOXP1, a winged helix/forkhead transcription factor, as a critical effector of PRMT5-induced B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 47 publications
3
127
0
Order By: Relevance
“…The PRMT5 gene encodes an arginine methyltransferase, which catalyzes the transfer of methyl groups to the amino acid arginine in target proteins, including histones, and promotes target gene transcription. A wealth of literature supports the view that PRMT5 plays a vital role in regulating cancer progression via histone methylation 49 - 51 . PRMT5 promotes the cancer stem cell function of breast cancer by enhancing the enrichment of H3K4me3 on the FOXP1 promoter and subsequently driving FOXP1 transcription and expression 49 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The PRMT5 gene encodes an arginine methyltransferase, which catalyzes the transfer of methyl groups to the amino acid arginine in target proteins, including histones, and promotes target gene transcription. A wealth of literature supports the view that PRMT5 plays a vital role in regulating cancer progression via histone methylation 49 - 51 . PRMT5 promotes the cancer stem cell function of breast cancer by enhancing the enrichment of H3K4me3 on the FOXP1 promoter and subsequently driving FOXP1 transcription and expression 49 .…”
Section: Discussionmentioning
confidence: 89%
“…A wealth of literature supports the view that PRMT5 plays a vital role in regulating cancer progression via histone methylation 49 - 51 . PRMT5 promotes the cancer stem cell function of breast cancer by enhancing the enrichment of H3K4me3 on the FOXP1 promoter and subsequently driving FOXP1 transcription and expression 49 . SHARPIN augments invasiveness of lung cancer by interacting with PRMT5, which methylates histones H3 and H4, subsequently upregulating metastasis-related gene expression 50 .…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, phosphorylation of MEP50 on Thr5 increases the methyltransferase activity of PRMT5‐MEP50 toward histone H4 . In BCSCs, PRMT5 was reported to interact with FOXP1, and authors speculated that the interaction could be targeted using small inhibitor molecules . This was recently applied in mantle cell lymphoma, in which a selective PRMT5 inhibitor was generated offering a promising therapeutic strategy …”
Section: Introductionmentioning
confidence: 99%
“…25 In BCSCs, PRMT5 was reported to interact with FOXP1, and authors speculated that the interaction could be targeted using small inhibitor molecules. 18 This was recently applied in mantle cell lymphoma, in which a selective PRMT5 inhibitor was generated offering a promising therapeutic strategy. 26 Here, based on the analysis of a large cohort of patients with breast tumors, we identified a new PRMT5 interactor, the liver kinase B1 protein (LKB1), a master kinase that acts as a key regulator of cell polarity, energy metabolism and mTOR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The PRMT5-WDR 77 activity is necessary for TGF-β dependent EMT and metastatic processes that are associated with (i) PRMT-dependent R2 methylation and (ii) regulation of critical genes linked with TGF-beta-dependent cancer cell invasion pathways (Chen et al 2017). Chiang et al (2017) reported PRMT5 recruitment to the FOXP1 promoter drives breast cancer stem cell (BCSC) proliferation facilitated by H3R2 dimethylation and H3K4 trimethylation (Chiang et al 2017). They further discussed the implications of inhibiting PRMT5 on BCSC stem cells and potential for decreasing rates of tumour relapse (Chiang & Davies 2018).…”
Section: Protein Arginine Methyltransferasementioning
confidence: 99%